Blue jean Buddha : voices of young Buddhists - Loundon, Sumi . (Boston : Wisdom Publications, 2001)
Here are real stories about young Buddhists in their own words that affirm and inform the young adult Buddhist experience of trying to live in the modern world, and bring Buddhism into their lives.
Keywords: Buddhist youth -- Biography. -- United States; Spiritual biography -- United States; Buddhist youth -- Religious life -- United States